1996
DOI: 10.1161/01.cir.94.11.2768
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular, Peripheral Vascular, and Neurohumoral Responses to Mental Stress in Normal Middle-Aged Men and Women

Abstract: Mental stress in the laboratory results in a substantial sympathetic response in normal middle-aged and older men and women, but EF commonly falls because of a concomitant rise in afterload. These results provide essential age- and sex-matched reference data for studies of mental stress-induced ischemia in patients with coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
2
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(67 citation statements)
references
References 27 publications
6
55
2
4
Order By: Relevance
“…Another mental stress-associated arrhythmogenic factor may be sympatho-adrenergic activation, which has been demonstrated in the laboratory setting by measuring increase of norepinephrine levels during mental stress. 31,32 Physical Stress, Sexual Activity, and Tachyarrhythmias…”
Section: Mental Stress and Tachyarrhythmiasmentioning
confidence: 99%
“…Another mental stress-associated arrhythmogenic factor may be sympatho-adrenergic activation, which has been demonstrated in the laboratory setting by measuring increase of norepinephrine levels during mental stress. 31,32 Physical Stress, Sexual Activity, and Tachyarrhythmias…”
Section: Mental Stress and Tachyarrhythmiasmentioning
confidence: 99%
“…We and others had also shown that decreased ejection fraction in response to mental stress in many cases does indicate ischemia, but that a substantial proportion of normals also have ejection fraction decreases, probably as a reflection of increased afterload rather than ischemia. 3,4 Because ejection fraction decrease does not appear to be a highly specific marker of ischemia in response to mental stress, it is not surprising that the PIMI data did not associate ejection fraction changes with increased mortality risk. Changes in blood pressure, heart rate, and catecholamines occur with mental stress, but do not differentiate people with myocardial ischemia from those without.…”
Section: Responsementioning
confidence: 99%
“…The subject's task was to designate the color in which each word is presented as quickly as possible. This program was implemented in the Psychophysiological Investigations of Myocardial Ischemia Study (PIMI; Becker et al, 1996;Goldberg et al, 1996).…”
Section: Stroop Color-word Taskmentioning
confidence: 99%